Implementasi Hukum Adat dalam Penyelesaian Sengketa Lingkungan: Studi Etnografis di Kawasan Hutan Adat - Pertiwi, Putri; Sakdiyah, Faridatus; Rian, Feryll Anugrah (Universitas Sains dan Teknologi Komputer, 2024)
Customary law plays a vital role in resolving environmental disputes in customary forest areas, which are often focal points of conflict among indigenous communities, the government, and private companies. This study aims to explore the effectiveness of customary law in resolving environmental disputes, identify challenges in its implementation, and provide recommendations for strengthening customary law in the future. Using a qualitative approach and ethnographic methods, this research collected data through in-depth interviews, participatory observations, and document analysis in several customary forest areas in Kalimantan and Sumatra. The results reveal that 75% of disputes were resolved through customary deliberation mechanisms, reflecting the restorative justice values and collectivism of indigenous communities. However, the implementation of customary law faces significant challenges, including a lack of formal recognition by the government, global economic pressures, and limited supporting infrastructure. Indigenous communities expressed high satisfaction with customary law, which they perceive as more aligned with local values compared to formal legal systems. This research contributes by highlighting the importance of formal recognition and integration of customary law into the national legal framework without compromising local autonomy. The findings align with international studies showing that recognition of customary law can enhance conflict management and environmental conservation. The implications of this study emphasize the need to strengthen customary law recognition through policy reforms and the use of technologies such as GIS and blockchain to document indigenous claims. Thus, this study provides a foundation for policymakers to prioritize strengthening customary law as a sustainable mechanism for resolving environmental disputes.